In vitro Activity of a New Fourth-Generation Cephalosporin, Cefoselis, Against Clinically Important Bacterial Pathogens in China - Cheng, Jing-Wei; Su, Jian-Rong; Xiao, Meng; Yu, Shu-Ying; Zhang, Ge; Zhang, Jing-Jia; Yang, Yang; Duan, Si-Meng; Kudinha, Timothy; Yang, Qi-Wen; Xu, Ying-Chun (Frontiers in Microbiology, 2020)
The objective of this study was to systematically evaluate the in vitro activity of cefoselis and other comparators against common bacterial pathogens in China. Bacterial clinical isolates (n = 1188), including Enterobacteriaceae, non-fermentative Gram-negative organisms, methicillin-resistant S. aureus (MRSA), methicillin-sensitive S. aureus (MSSA) and Streptococcus spp., were collected from 18 hospitals across China (Jan 2014 - Dec 2016). Minimum inhibitory concentrations (MICs) were determined by broth microdilution method. Phenotypic identification of extended-spectrum β-lactamase (ESBL) production was carried out as recommended by the Clinical and Laboratory Standards Institute (CLSI). Cefoselis showed poor activity against ESBL producing- E. coli, K. pneumoniae and P. mirabilis, with susceptibility rates of <10% each, while the susceptibility rates of this antibiotic against non-ESBL producing strains of these organisms were 100%, 94.3% and 97.0%, respectively. Cefoselis exhibited susceptibility rates of 56.7%-83.3% against other Enterobacteriaceae isolates including C. freundii, E. aerogenes, E. cloacae, S. marcescens and P. vulgaris. For A. baumannii and P. aeruginosa isolates tested, the susceptibility rates to cefoselis were 18.7% and 73.3%, respectively. All MRSA strains were resistant to cefoselis whilst all MSSA strains were susceptible to this antibiotic. Against penicillin-susceptible S. pneumoniae (PSSP), penicillin-resistant S. pneumoniae (PRSP), beta-hemolytic streptococci, and Viridans group streptococci strains, cefoselis showed susceptibility rates of 96%, 63.3%, 92.6% and 100.0%, respectively. In conclusion, cefoselis showed good activity against non-ESBL producing- E. coli, K. pneumoniae, and P. mirabilis, MSSA, Streptococcus spp., and was also potent against other Enterobacteriaceae and P. aeruginosa.